Utilization Pattern of Information Communication Technologies (ICTs) among Farmers of District Kannauj in Uttar Pradesh - Mishra, Yagya Dev; Mishra, Reeta (Indian Journal of Extension Education, 2016)
The research study was conducted in 11 villages of district Kannauj in central Uttar Pradesh. Asurvey was done among a  selected sample of 126 farmers with the help of an interview schedule. The farmers were asked questions regarding their  usage pattern of various ICT tools. The findings of the study reveal that a sizeable number of farmers possess mobile  phones, radio and television at home. Few farmers also have access to the computer and internet through the younger  members of their family. The mass media (both radio and television) is popularly used for news and entertainment. Afew  respondents used to watch/listen agricultural programmes on TV/radio. It is important to note that a sizable number of  farmers are aware of the SMS services being offered by the KVK and other departments for agricultural related advice.  The computer and internet access was found to be in infantry stage in the villages, but farmers were aware that in future  each and every problem can be solved through computer. The frequent interruption in power supply, difficulty in technical  content, odd timings of broadcasting/telecasting are the major causes stated by the farmers for low popularity of  broadcasting media. Radio remains a popular medium for weather and market related information. The older farmers  facing limitations of language and technological barriers in operating mobile and internet.
Keywords: information communication technologies; (ICTs); utilization pattern; rural society